2010
DOI: 10.1136/ard.2010.139618
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of synovitis with contrast-enhanced MRI using a whole-joint semiquantitative scoring system in people with, or at high risk of, knee osteoarthritis: the MOST study

Abstract: Objectives To introduce a comprehensive and reliable scoring system for the assessment of whole-knee joint synovitis based on contrast-enhanced (CE) MRI. Methods Multicenter Osteoarthritis Study (MOST) is a cohort study of people with, or at high risk of, knee osteoarthritis (OA). Subjects are an unselected subset of MOST who volunteered for CE-MRI. Synovitis was assessed at 11 sites of the joint. Synovial thickness was scored semiquantitatively: grade 0 (<2 mm), grade 1 (2–4 mm) and grade 2 (>4 mm) at each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
149
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(161 citation statements)
references
References 21 publications
4
149
0
1
Order By: Relevance
“…Whether aggressive treatment of inflammation reduces the risk for knee replacement will have to be shown in subsequent randomized studies. We acknowledge that assessment of Hoffa signal intensity changes as a surrogate for synovitis is an inferior measure when compared with contrast material-enhanced imaging, especially owing to its nonspecificity (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Whether aggressive treatment of inflammation reduces the risk for knee replacement will have to be shown in subsequent randomized studies. We acknowledge that assessment of Hoffa signal intensity changes as a surrogate for synovitis is an inferior measure when compared with contrast material-enhanced imaging, especially owing to its nonspecificity (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…The total synovitis score of 11 sites was calculated (range 0e22). A total score of 0e4 was considered normal (no synovitis); 5e8 represents a mild, 9e12 a moderate and above 13 a severe synovitis 13 . Intra-class correlation (ICC) was based on a random sample of 15% Gd-chelate enhanced MR images and was 0.93 for synovitis and 0.90 for synovitis change.…”
Section: Mri Scoringmentioning
confidence: 99%
“…As synovitis is known to be patchy and heterogeneous 11 , a synovitis scoring method on magnetic resonance imaging (MRI) should encompass a sufficient number of compartments. The synovitis scoring method developed by Guermazi et al 13 is a comprehensible and practical method, which meets these requirements and compares well with synovial inflammation in tissue biopsies of knee OA patients 8 .…”
Section: Introductionmentioning
confidence: 99%
“…A recent report showed that synovitis detected by contrast-enhanced MRI had a strong association (adjusted odds ratio 9.2) with at least moderate severity of knee pain as assessed by the Western Ontario and McMaster Osteoarthritis Index pain scale [169]. A comprehensive whole-knee joint synovitis scoring system has been proposed recently, which showed a high reliability based on contrast-enhanced MRI [170]. Interventional studies assessing intraarticular corticosteroids or NSAIDs and paracetamol demonstrated associations between decreased synovitis and reduction of pain in patients with knee OA [171,172].…”
Section: Mri In Osteoarthritismentioning
confidence: 99%